Aqueous Plant Extracts Increase Nanocrystalline Fe3O4/g-Fe2O3 to a-Fe2O3 Transition Temperature: Insights into Traditional Calcination Process for Herbometallic Preparation - Krishnamachary, Balaji; Pemiah, Brindha; Krishnaswamy, Sridharan; Maheswari Krishnan, Uma; Sethuraman, Swaminathan; Rajan, K.S. (Asian Journal of Chemistry, 2014)
A unique method of calcination for preparation of drugs from metallic and herbal ingredients has been in vogue in India since several centuries ago; however the same is not completely understood. Our experiments show that during the preparation of an iron-based herbometallic drug, transition from Fe3O4/g-Fe2O3 to a-Fe2O3 is delayed to higher temperatures due to addition of light metals from the aqueous extracts of Indian gooseberry, Belleric myrobalans and Chebulic myrobalans. The repeated calcination cycles increase the composition of essential elements like potassium, sodium and calcium, while increasing the crystallinity of Fe3O4/g-Fe2O3.